Contemporary poetic cinema through the lens of traditional Chinese poetics - Wei, William Hong-xiao (The University of Edinburgh, 2023)
This thesis investigates the aesthetics of contemporary poetic cinema by Alexander Sokurov, Wong Kar-wai and Terrence Malick within a framework of ancient Chinese theories of poetry. I compare these theories to some other theoretical perspectives, such as Edmund Husserl’s phenomenology, auteur theory, expression theories of art and Rudolf Arnhem’s film aesthetics. I also consider film theorists’ continued emphasis on emotion and feelings in a discussion of cinematic specificity, and film phenomenologists’ considerations of objects, moods, sensations and atmospheres. I demonstrate that in some films by Sokurov, Wong and Malick, their presentation of ethereal realms, romantic and erotic relationships, and of a conjunction of macrocosm and microcosm fall under the categories of “lofty and ancient”, “intricate sensuality”, and “flowing movement”. I maintain that art moods in cinema are discernibly distinct from human emotions as discussed in cognitive film theory. I ascribe film moods to a filmmaker’s artistic expression of individuality and world view, a film’s stylised and aesthetic presentation of experiential worlds, as well as the audience’s experiences of the film. Drawing on the critical philosophical and aesthetic concepts of “heart-mind” (xin心), “intents” (zhi志), “affections” (qing情) and qi氣in ancient Chinese thought, my analysis of these films contends that poetic cinema records, manifests and offers bodily, sensual, emotional and intellectual experiences, as part of the physical world’s richness, vibrancy and concreteness, with which our subjective states are deeply interconnected. Paramount to my enquiry into poetic cinema, therefore, is the ways in which the cinematic medium can be deployed both to express and to evoke subjective feelings in the spectator. My central point is that the aesthetic categories outlined in ancient Chinese poetics help identify potential candidates for the genre of poetic cinema in accordance with the classification of moods in the Chinese poetic tradition.
Keywords: Contemporary Poetic Cinema; Traditional Chinese Poetics; Alexander Sokurov; Wong Kar-wai; Terrence Malick; ancient Chinese theories of poetry; film phenomenologists